1985
DOI: 10.2170/jjphysiol.35.933
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ca2+-dependent Cl- and K+ conductances in rat and mouse parotid acinar cells.

Abstract: Isolated acinar cells from rat and mouse parotid glands were studied with patch-clamp whole-cell current recordings. Acetylcholine (ACh) stimulation caused a transient inward current at a membrane potential of -70 mV, and a sustained outward current at a membrane potential of 0 mV, in quasi physiological Nat, K+ ion gradients, except the zero-C1-ion gradient condition across the membrane. The reversal potential obtained from the ACh-evoked steady current was about -75 mV, in this ionic condition. When major Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
26
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 19 publications
4
26
0
Order By: Relevance
“…Taken together with previous data (6,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), these results indicate that a rise in [Ca2+], is in fact necessary to activate basolateral membrane K+ conductance. The blunted response of Me2BAPTA-loaded cells ( Fig.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…Taken together with previous data (6,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), these results indicate that a rise in [Ca2+], is in fact necessary to activate basolateral membrane K+ conductance. The blunted response of Me2BAPTA-loaded cells ( Fig.…”
Section: Methodssupporting
confidence: 87%
“…(ii) the cellular K+ loss is abolished in Ca2+-depleted cells stimulated in Ca2+-free medium (22,23), (iii) the application of Ca2" ionophores to acinar cells activates K+ channels and causes a loss of cellular K+ similar to that caused by agonists (23)(24)(25)(26), (iv) the intracellular perfusion of a Ca2+ chelator blocks the agonist-stimulated increase in K+ conductance (18,26,27), and (v) the intracellular perfusion of inositol trisphosphate activates the K+ conductance (28).…”
mentioning
confidence: 99%
“…Salivary gland acinar cells are no exception, expressing at least five distinct chloride conductances (18,19). The first of these to be characterized (20) is activated by an increase in intracellular free [Ca 2ϩ ] i (21). It is likely that the Ca 2ϩ -dependent Cl Ϫ channel is targeted to the apical membrane in parotid acinar cells as has been shown in pancreatic acinar cells (22).…”
mentioning
confidence: 99%
“…It has been suggested, however, by a number of other studies using whole cell patch-clamp techniques or K ϩ (and Rb ϩ ) efflux measurements that K Ca channels, distinct from maxi-K ϩ channels, may also contribute significantly to the outward K ϩ current in the acinar cells of various salivary glands including rat parotid (29,46), sheep parotid (20,55), bovine parotid (34), rat mandibular (26,27), and mouse mandibular glands (22). These studies have shown that a maxi-K ϩ channel blocker, TEA, is largely ineffective in inhibiting muscarinically or Ca 2ϩ -evoked K ϩ conductance.…”
mentioning
confidence: 99%